Short-term exposure to elevated CO2 stimulates growth and metabolic responses that alleviate early-stage iron deficiency symptoms in soybean - Soares, José C.; Pintado, Manuela; Vasconcelos, Marta W. (Journal of plant interactions, 2022)
Elevated CO 2 (eCO 2 ) increase plant biomass and might lead to nutritional losses. The results showed that eCO 2 under Fe-deficiency stimulates root dry weight from 0.37-0.80 g plant −1 and shoot dry weight from 0.82-2.10 g plant −1 , without compromising root/shoot ratio. Besides, eCO 2 improved the chlorophyl content of Fe-deficient plants. However, downregulation of photosynthesis, reduction in stomatal conductance and transpiration rate, and an increase in water-use efficiency was observed due to eCO 2 . Moreover, under Fe-deficiency, eCO 2 decreased K and Mg in roots, and Mg in leaves, whereas increased P and Zn in roots and leaves. In Fe-sufficient plants, eCO 2 increased K, P, Mn, Zn and Fe in leaves and did not change the concentration in roots. The Fe-deficiency-induced responses in roots, including the increase in FCR activity, and the expression of Fe-uptake genes were stimulated by eCO 2 , but were not sufficient to increase Fe concentration in Fe-deficient plants.